2022
DOI: 10.3390/molecules27238550
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aflatoxin B1 Synthesis in Aspergillus flavus by Mate (Ilex paraguariensis), Rosemary (Rosmarinus officinalis) and Green Tea (Camellia sinensis) Extracts: Relation with Extract Antioxidant Capacity and Fungal Oxidative Stress Response Modulation

Abstract: Plant extracts may represent an ecofriendly alternative to chemical fungicides to limit aflatoxin B1 (AFB1) contamination of foods and feeds. Mate (Ilex paraguariensis), rosemary (Romarinus officinalis) and green tea (Camellia sinensis) are well known for their beneficial properties, which are mainly related to their richness in bioactive phenolic compounds. AFB1 production is inhibited, with varying efficiency, by acetone/water extracts from these three plants. At 0.45 µg dry matter (DM)/mL of culture medium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Phenolics, in particular phenolic acids and flavonoids, have been reported to exhibit important antifungal properties in several plant species and against a wide variety of pathogenic fungi (e.g., [ 48 , 49 ]). Moreover, various studies have shown the ability of these compounds to inhibit the biosynthesis of various mycotoxins, namely AFs (e.g., [ 50 , 51 , 52 ]). Consistent with this are the findings of the study conducted on rice by Giorni et al [ 53 ], in which it was observed that the TPC and phenolic profile varied significantly depending on the level of fungal infestation and the presence of mycotoxins.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolics, in particular phenolic acids and flavonoids, have been reported to exhibit important antifungal properties in several plant species and against a wide variety of pathogenic fungi (e.g., [ 48 , 49 ]). Moreover, various studies have shown the ability of these compounds to inhibit the biosynthesis of various mycotoxins, namely AFs (e.g., [ 50 , 51 , 52 ]). Consistent with this are the findings of the study conducted on rice by Giorni et al [ 53 ], in which it was observed that the TPC and phenolic profile varied significantly depending on the level of fungal infestation and the presence of mycotoxins.…”
Section: Resultsmentioning
confidence: 99%